The Political Participation of Fishermen’s Wives in Surabaya City, East Java, Indonesia with Human Action Planning (Journal of Governance and Development (JGD), 2014)
Political participation of ï¬ shermenâ€™s wives in the coastal areas of Surabaya City, East Java, Indonesia is indicated low. The ï¬ shermanâ€™s wives are very passive both in the politics and in inï¬‚ uencing the public policy. This condition contrasts with Indonesian government policies that has to protect and to encourage the political participation of women in the country, as evidenced by the promulgation of act No. 31 of 2002 on political parties and law No. 12 of 2003. This research aims to know the causes of political participation in Surabaya City, East Java, Indonesia and to ï¬ nd out the ways to increase their political participation. The research shows the causes of the political participation of in Surabaya City, East Java, Indonesia are both internal and eksternal factors. Internal factors consists of the minimum ï¬ shermenâ€™s wives education, skill and organization experience, and also double-status and reproduction function they have. Eksternal factors includes patriarchy culture and the absence of the society achievement for them who are active in organization. The analysis sugests that to ensure the political participation of ï¬ shermenâ€™s wives in Surabaya City, East Java, Indonesia is using the the mixture of utonomous and mobilization ways, evethough the autonomous way is more preferable, considering their motives to participate are psicological and social motives, rather than economic and political ones. These points are included the human action planning approach in development. The people as a subject of development, not as an object.